Una muerte solitaria : el segundo caso del sheriff Walt Longmire - Johnson, Craig, 1961-; Porras Sánchez, María; Johnson, Craig, 1961- (Madrid : Siruela, 2013)
Sheriff Walt Longmire finds unspeakable viciousness in Wyomingas Big Horn Mountains Craig Johnson garnered both praise and an enthusiastic readership with his acclaimed debut novel featuring Sheriff Walt Longmire, "The Cold Dish." Now Johnson takes us back to the rugged landscape of Absaroka County, Wyoming, for "Death Without Company." When Mari Baroja is found poisoned at the Durant Home for Assisted Living, Sheriff Longmire is drawn into an investigation that reaches fifty years into the mysterious womans dramatic Basque past. Aided by his friend Henry Standing Bear, Deputy Victoria Moretti, and newcomer Santiago Saizarbitoria, Sheriff Longmire must connect the specter of the past to the present to find the killer among them.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: Longmire, Walt -- Fiction; Sheriffs -- Fiction; Bighorn Mountains (Wyo. and Mont.) -- Fiction; Wyoming -- Fiction; Detective and mystery fiction; Electronic books